Development of a cell-seeded construct for osteochondral modelling and repair - Popov, Alexander A. (2016)
Regenerative therapeutic solutions are required to address the increasing prevalence of bone and cartilage diseases within the population. Limitations of existing treatments, such as bone graft reconstructions or biomaterial implants, suggest that osteochondral tissue constructs with the ability to support differentiation of mesenchymal stem cells into both osteoblast and chondrocyte lineages is desirable. To date, tissue-engineering approaches have focused on developing individual scaffolds for each osteochondral lineage. Constructs are combined once tissues have developed sufficiently. Unfortunately, delimitation often occurs under normal physiological loading and implants fail.